Resistance of Women Survivors of Sexual Violence in Social Media - Riskiyah, Faridatur; Al-Uyun, Dhia (UIN Sunan Kudus, 2022)
This research focuses on the forms of resistance developed by women survivors of Technology-Facilitated Sexual Violence (TFSV) or Kekerasan Gender Berbasis Siber (KGBS) on social media. This research aims to describe and analyze those forms of resistance. This paper uses the resistance theory of James Scott to identify forms of victim resistance and uses SWOT analysis to evaluate the results that have been carried out. The samples of this research are social media users, specifically on Instagram and Twitter, and public figures who were experiencing sexual violence on those media. This qualitative research has been conducted with a gender perspective and primary data as a data collection. The results showed that the forms of women's resistance were public education through social media, prosecuting and threatening perpetrators, and self-acceptance. Based on SWOT analysis, these resistance forms have enabled victims to expose cases of sexual violence in cyberspace using social media and open dialogue with social media, and increase public awareness. This research seeks to show a tangible form of women's resistance to sexual violence on social media. Although it cannot eliminate patriarchal culture in society's view of sexual violence, these forms of women's resistance can affect people effectively so that gradually people can recognize forms of sexual violence in cyberspace and no longer blame the victim.Keywords : TFSV, resistance, women studies, public figure